Neurotic Generation of Covid-19 in Eastern Europe - Długosz, Piotr; Kryvachuk, Liudmyla (Frontiers in Psychiatry, 2021)
This article presents the results of a research survey, which shows the relationship between neuroticism and the coronavirus pandemic, which was performed among students in Poland and Ukraine. The survey was conducted online, on a sample of 1,978 respondents in Poland and 411 in Ukraine. The results indicated that average and high levels of neuroticism were observed among 61% of respondents in Poland and 47% in Ukraine. Regression analysis revealed that the main factors correlated with the level of neuroticism were educational burnout, gender, financial situation, interest in the pandemic, and satisfaction with life. As indicated by the respondents, neuroticism increases with educational burnout, loss of economic resources, and an increase of interest in the pandemic. Moreover, it was observed that female respondents scored higher on the scale of neuroticism compared to males. Comparative analyses between the Polish and Ukrainian students indicated that the Ukrainian youth cope with quarantine and distance education better and have better mental health. The overall responses showed that in the conditions of a pandemic, neuroticism may increase among the young generation. Keywords: COVID-19, neuroticism, stress, educational burnout, students, Poland and Ukraine